Water and sediment qualities of Ekole river, Bayelsa state, Nigeria (2004)
A study was carried out to determine the physico-chemical characteristics and heavy metal contents of the water and sediment of Ekole river in Bayelsa state, Nigeria. Water and sediment samples were collected in the dry (december/ January) and wet (June/July) seasons during 2003 and 2004. Surface water up to 15cm depth and sediments were sampled at nine locations: 100, 200, 400, 500m upstream; 0, 100, 200, 300, 400m downstream of an oil flow station. The samples were anlyzed for total suspended solids (TSS), pH, chloride, dissolved oxygen, conductivity and heavy metals. These parameters were either measured in-situ using approriate meters or analysed in the laboratory using standard methods. The results obtained were compared with the baseline ecological data for 'Gbaran Extended Field'. upstream of the study of the area. World Health Organization and the Federal Environment Protection Agency's standards for water quality. The results showed increase TSS. pH and conductivity of the water over the baseline data. All heavy metals of interest: cadmium(Cd), lead (Pb), mangaese (Mn) zinc(Zn), nickel(Ni) copper, (Cu), iron (Fe) and chromium (Cr) were present in the water while Ni, Cd and Cr, absent in the baseline data were detected. Significant increases (p<0.05) were recorded for iron, zinc, copper and managese over baseline data. Higher concerntrations (p<0.05) of heavy metals were recorded in sediments than water and the dominant metal was iron. It was concluded that changes in water quality had occured in Ekole river near Obama flow station and the need to adhere to existing environmental laws and regular monitoring recommended.